Integrative single-cell and metagenomic analysis dissects SARS-CoV-2 shedding modes in human respiratory tract - Xiangxing Jin; Lili Ren; Xianwen Ren; Jianwei Wang (Biosafety and Health)
It is crucial to understand how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sheds in human respiratory tract, but this question remains elusive due to technical limitations. In this study, we integrated published human metagenomic data of SARS-CoV-2 and developed a novel algorithm named RedeCoronaVS to systematically dissect SARS-CoV-2 shedding modes with single-cell data as reference. Our study demonstrated that SARS-CoV-2 particles were the dominant mode of viral shedding in the very early infection phase (≤24 h after hospitalization). Within the first week after hospitalization, SARS-CoV-2 replicas within host cells dominated viral shedding alongside viral particles. One week later, viral fragments became the dominant mode in patients with mild or moderate symptoms, while viral replicas still dominated in some patients with severe symptoms. In addition to epithelial cells, SARS-CoV-2 replicas in neutrophils, macrophages, and plasma cells also played significant roles and were associated with sampling time and disease severity.